2009
DOI: 10.1016/j.adolescence.2009.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐cultural invariance of the Academic Expectations Stress Inventory: Adolescent samples from Canada and Singapore

Abstract: We provide further evidence for the two‐factor structure of the 9‐item Academic Expectations Stress Inventory (AESI) using confirmatory factor analysis on a sample of 289 Canadian adolescents and 310 Singaporean adolescents. Examination of measurement invariance tests the assumption that the model underlying a set of scores is directly comparable across groups. This study also examined the cross‐cultural validity of the AESI using multigroup confirmatory factor analysis across both the Canadian and Singaporean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 34 publications
1
55
0
Order By: Relevance
“…Recent studies have shown that in Singapore society, which has a strong inclination towards the Confucian ideals of filial piety, obedience, loyalty, and collectivism, students develop school-related anxieties. In many ways, these anxieties are due to the expectations and pressures placed on them by parents, who consider children's school success as a matter of pride for the family and country (Anderson & Mayes, 2010;Ang & Huan, 2006;Ang et al, 2009;Lowe & Ang, 2012;Tan & Yates, 2011). Parents in Singapore have high academic expectations and are concerned about their child's achievements, beginning at the preschool age (Ebbeck & Gokhale, 2004;Sharpe, 2000, p. 123).…”
Section: Who and What Of Children In Singapore?mentioning
confidence: 96%
“…Recent studies have shown that in Singapore society, which has a strong inclination towards the Confucian ideals of filial piety, obedience, loyalty, and collectivism, students develop school-related anxieties. In many ways, these anxieties are due to the expectations and pressures placed on them by parents, who consider children's school success as a matter of pride for the family and country (Anderson & Mayes, 2010;Ang & Huan, 2006;Ang et al, 2009;Lowe & Ang, 2012;Tan & Yates, 2011). Parents in Singapore have high academic expectations and are concerned about their child's achievements, beginning at the preschool age (Ebbeck & Gokhale, 2004;Sharpe, 2000, p. 123).…”
Section: Who and What Of Children In Singapore?mentioning
confidence: 96%
“…Singapore and other Asian societies have been found to be higher on the cultural dimension of collectivism [24,25]. Additionally, the stress arising from academic pressure to excel has also been documented in Asian societies [19,20]. Although Singapore and the US differ in many ways, both are among the 42 nations ranked with ''very high human development'' by the Human Development Index (HDI) and show similar levels of life expectancy, literacy rates, and gross national income per capita [26].…”
Section: Introductionmentioning
confidence: 97%
“…Singapore's Ministry of Education (MOE) has a strong mission of striving towards excellence. Likewise, Singaporean parents consider schooling of primary importance, and they hold high expectations for their children's educational achievement, sometimes resulting in academic pressure and stress faced by these children [19,20]. Within the MOE, there is provision for psychological assessment and services for children with learning, behavioral and emotional problems.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, students appreciate the fact that examination grades are the most important aspect of their school life. However, the process of preparing for examinations was reported to be the most stressful event of their school life (Ang & Huan, 2006;Ang, et al, 2009;Dobson, 1980).…”
Section: Introductionmentioning
confidence: 99%